A democracia capturada: poder econômico poluidor da democracia brasileira: sistemas de controle - Santos, Raquel Cunha dos (2017)
This dissertation seeks to answer to what extent democracy in Brazil is safe from the predatory influence of economic power, whenever denoted the misused use of this social force. Initially it discusses the origin of democracy and its functioning, as well as how this institute was incorporated by the Brazilian Constitution of 1988 - by studying its principles, its instruments of pressure and risks of capture. Then there is a deep analysis of the democratic constitutional arrangement, pointing out its relation between political rights and citizenship, the legislator's option for the semi-direct democracy, the constitutional electoral principles and how the system of government is arranged. The subject of this work advances in the analysis of mechanisms to defend democracy by considering, foremost, the distortion factors to then verify the forms to promote its prophylaxis.